Inside The O2: the NHS Nightingale Hospital London education center. Issue 5 (2nd September 2020) - Bushell, Verity; Thomas, Libby; Combes, Julie
ABSTRACT: As part of the response to COVID-19 in the United Kingdom (UK) the NHS Nightingale Hospital London was rapidly established in March 2020. Set up in the ExCel, an international conference center, it aimed to address the anticipated shortfall of intensive care beds in London. Whilst this hospital garnered huge amounts of publicity in the UK, less widely discussed is the Nightingale Education Center. The education center was instrumental in ensuring that there were staff across all professions ready to work there and had interprofessional education at its core. In a period of under two months it inducted and upskilled over 2, 500 people from multiple healthcare and non-healthcare professions. That is more than most hospitals would induct in a whole year. To complete interprofessional training on this scale the education center decamped from the ExCel to The O2, a 20, 000 capacity arena, and remained there for six weeks beating the iconic artist Prince for the title of longest running residency. This report offers a reflection on the authors' time spent working in the Education Center as members of the 'Core Operations' team. The content of the article is based upon the authors' reflections, first-hand experiences and field observations. It offers a reflection upon the massive undertaking of setting up an education center in an entertainment venue, as well as the successes and challenges of working interprofessionally in this unique space and under pandemic conditions.